Activation of plasmacytoid dendritic cells and B cells with two structurally different Toll‐like receptor 7 agonists. (13th April 2020) - Berggren, Olof; Pucholt, Pascal; Amcoff, Cane; Rönnblom, Lars; Eloranta, Maija‐Leena
Abstract: Synthetic Toll‐like receptor (TLR) 7 agonists have been suggested as immune modulators in a range of conditions. In contrast, self‐derived TLR7 activators, such as RNA‐containing immune complexes (RNA‐IC), can contribute to autoimmune diseases due to endogenous immune activation. The exact difference in immune cell response between synthetic and endogenous TLR7 triggers is only partly known. An understanding of these differences could aid in the development of new therapeutic agents and provide insights into autoimmune disease mechanisms. We therefore compared the stimulatory capacity of two TLR7 agonists, RNA‐IC and a synthetic small molecule DSR‐6434, on blood leucocytes, plasmacytoid dendritic cells (pDCs) and B cells from healthy individuals. IFN‐α, IL‐6, IL‐8 and TNF levels were measured by immunoassays, and gene expression in pDCs was analysed by an expression array. DSR‐6434 triggered 20‐fold lower levels of IFN‐α by pDCs, but higher production of IL‐6, IL‐8 and TNF, compared to RNA‐IC. Furthermore, IFN‐α and TNF production were increased with exogenous IFN‐α2b priming, whereas IL‐8 synthesis by B cells was reduced for both stimuli. Cocultivation of pDCs and B cells increased the RNA‐IC‐stimulated IFN‐α and TNF levels, while only IL‐6 production was enhanced in the DSR‐6434‐stimulated cocultures. When comparing pDCs stimulated with RNA‐IC and DSR‐6434, twelve genes were differentially expressed (log2 fold change >2, adjusted P ‐value <.05). In conclusion, RNA‐IC, which mimics an endogenous TLR7 stimulator, and the synthetic TLR7 agonist DSR‐6434 trigger distinct inflammatory profiles in immune cells. This demonstrates the importance of using relevant stimuli when targeting the TLR7 pathway for therapeutic purposes.